Mobile-bearing lateral unicompartmental knee replacement with the Oxford domed tibial component - Streit, Marcus R.; Walker, Tilman; Bruckner, Thomas; Merle, Christian; Kretzer, Jan Philippe; Gotterbarm, Tobias (Journal of bone and joint surgery. B, British volume, 2012)
The Oxford mobile-bearing unicompartmental knee replacement (UKR) is an effective and safe treatment for osteoarthritis of the medial compartment. The results in the lateral compartment have been disappointing due to a high early rate of dislocation of the bearing. A series using a newly designed domed tibial component is reported.The first 50 consecutive domed lateral Oxford UKRs in 50 patients with a mean follow-up of three years (2.0 to 4.3) were included. Clinical scores were obtained prospectively and Kaplan-Meier survival analysis was performed for different endpoints. Radiological variables related to the position and alignment of the components were measured.One patient died and none was lost to follow-up. The cumulative incidence of dislocation was 6.2% (95% confidence interval (CI) 2.0 to 17.9) at three years. Survival using revision for any reason and aseptic revision was 94% (95% CI 82 to 98) and 96% (95% CI 85 to 99) at three years, respectively. Outcome scores, visual analogue scale for pain and maximum knee flexion showed a significant improvement (p < 0.001). The mean Oxford knee score was 43 (sd 5.3), the mean Objective American Knee Society score was 91 (sd 13.9) and the mean Functional American Knee Society score was 90 (sd 17.5). The mean maximum flexion was 127° (90° to 145°). Significant elevation of the lateral joint line as measured by the proximal tibial varus angle (p = 0.04) was evident in the dislocation group when compared with the non-dislocation group.Clinical results are excellent and short-term survival has improved when compared with earlier series. The risk of dislocation remains higher using a mobile-bearing UKR in the lateral compartment when compared with the medial compartment. Patients should be informed about this complication. To avoid dislocations, care must be taken not to elevate the lateral joint line.